Situações de Risco, Trabalho e Saúde de Imigrantes Brasileiros: representações sociais - Moreira, Maria Adelaide Silva Paredes (2007)
This study searches in approaching diverse pertinent aspects to the immigration process that affects the countries of the European Union especially in Portugal. The works deriving from this research has its objective in: analyzing the risk, work and health in Brazilian immigrants residing in Lisbon, Portugal. As methodological way, we use the instruments: Test of Free Association of Words and half-structuralized interview. For in such a way, they had been processed in software s for analysis between them: SPSS 14,5, Evoc, Trideux and Alceste. The not-boarded results in this study will be worked as clippings and will be sent for posterior publication. Thus, I consider this work enriching, in view of contributing of the same as mechanisms of understanding of being a immigrant and the possibility of the mobilization of the society and the academic environment for a phenomenon growing each time more, especially, the professionals of health, so we can intervine in a more necessary form within the factors that affects this population layer directly